Poverty in the European Community: Trends and debates - Graham Room (Intereconomics, 1988)
Economic insecurity and poverty represent a growing problem in the European Community today, with the re-emergence of absolute poverty on a scale unknown since the 1940's. Are we creating a new “underclass” in the midst of our still prosperous societies?
Keywords: 330; European Community